Translation Strategies in Indonesian Subtitle and Dubbing of The Greatest Showman - Yovita Jane; Julia Eka Rini (Institute of Research and Community Outreach - Petra Christian University, 2022)
Several studies have compared translation strategies to analyze subtitles and dubbing in movies, but few have compared the differences between the two mediums. This study compared the translation strategies used in movie subtitles and dubbing. Baker's (2018) translation strategies are used to analyze the Disney+ subtitle and dubbing of The Greatest Showman. Baker (2018) identifies 12 translation strategies used in the subtitle and dubbing: general word, more neutral/less expressive word, cultural substitution, loan word and explanation, paraphrase using related words, paraphrase using unrelated words, omission, idiom of similar meaning and form, idiom of similar meaning but dissimilar form, paraphrase, omission of a play on idiom, omission of entire idiom. One strategy, borrowing the source language idiom, employed by the dubbing is not found in the subtitle and one strategy, illustration, is not used in both. The fact that using the same strategy does not produce the same translation result shows that there are infinite interpretations. Keywords: translation strategies, subtitle, dubbing